Tumor Associated Macrophages-Friends Turned Foe? A Case Report and Review of Literature - Jairajpuri, Zeeba Shamim; Agarwal, Usha (Bangladesh Journal of Medical Science, 2012)
Most malignant tumors are infiltrated by inflammatory cells and it has long been considered that such infiltrates may be evidence of a host response to the tumor. Although lymphocytes are prominent in the inflammatory infiltrate, macrophages are also present, often in considerable numbers. Breast carcinoma is one such tumor where tumor associated macrophages (TAM) have been reported to be widespread, more so in Western literature. There is paucity of information about the biological and prognostic significance of this phenomenon in India. Ours is a tertiary center which receives approximately100 to120cases of breast carcinoma for pathological evaluation annually. Here we report the first case in our experience which showed large numbers of macrophages infiltrating the stroma around the tumor cells. DOI: http://dx.doi.org/10.3329/bjms.v11i2.8928 Bangladesh Journal of Medical Science Vol. 11 No. 02 April 2012: 139-142